Some practical methods for the conservation of soil moisture - Frowe, Arthur Lorenzo (My University, 1898)
Introduction: The problems confronting every wide-a-wake farmer of today are numerous, but there are few of greater importance to the Kansas farmer than the problem of the conservation of Soil Moisture; for whatever other conditions may be necessary to success, he must have moisture, and this is one thing, which if he has to depend upon rain for it he cannot always get when he needs it. Portions of our state, which when water can be supplied are very productive, yet because of its lack under present methods, are wothless for agricultural purposes. And even in the better portions, as well as, in other states, not seldom are crops materially injured by only a few weeks of drought at a critical time. If the crops could be tided over such periods, large losses might be avoided.
Citation: Frowe, Arthur Lorenzo. Some practical methods for the conservation of soil moisture. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Farmer; Soil Moisture; Agriculture; Kansas; Theses; Manuscripts (documents)